(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article examines the essence and nature of information and psychological influence on a person, analyzes the forms of influence, including destructive ones. Their active use in the Internet environment raises the question of the need for the formation and development of information and psychological security of the individual based on the management of social attitudes of a young person on the Internet.